دراسة الاختلافات الوراثية لأنواع نبات الداودي باستخدام مؤشرات AFLP - حسين, جَنان قاسم (Al-Nahrain Journal of Science, 2018)
The study was carried out at biotechnology laboratories- GCSAR- Syria in summer season 2010. The Amplified Fragment Length Polymorphism )AFLP( based on Polymerase Chain Reaction )PCR( with five primers were applied, was used to estimate fingerprinting and Genetic Distance for five cultivars of Chrysanthemum spp. )Incurved, Spidery, Reflexed, Anemone and Pompon(. Phases of work included, the isolation and purification of DNA plant parts and DNA polymorphisms were scored within amplified fragments by electrophoresis. The genetic analyses by using AFLP and Genetic Distance for Chrysanthemum cultivars genetic variability were determinately. High Genetic Distance Chrysanthemum cultivars (45.1%) in AFLP markers was registered between the two cultivars (Pompon X Incurved) and were found the lowest Genetic Distance )17.8%) between (Reflexed X Incurved) .